Salinity and high pH reduce denitrification rates by inhibiting denitrifying gene abundance in a saline-alkali soil - Yongchun Pan; Dongli She; Zhenqi Shi; Taohong Cao; Yongqiu Xia; Jun Shan (Scientific Reports, 2023)
Abstract Denitrification, as the main nitrogen (N) removal process in farmland drainage ditches in coastal areas, is significantly affected by saline-alkali conditions. To elucidate the effects of saline-alkali conditions on denitrification, incubation experiments with five salt and salt-alkali gradients and three nitrogen addition levels were conducted in a saline-alkali soil followed by determination of denitrification rates and the associated functional genes (i.e., nirK/nirS and nosZ Clade I) via N2/Ar technique in combination with qPCR. The results showed that denitrification rates were significantly decreased by 23.83–50.08%, 20.64–57.31% and 6.12–54.61% with salt gradient increasing from 1 to 3‰, 8‰, and 15‰ under 0.05‰, 0.10‰ and 0.15‰ urea addition conditions, respectively. Similarly, denitrification rates were significantly decreased by 44.57–63.24% with an increase of the salt-alkali gradient from 0.5 to 8‰. The abundance of nosZ decreased sharply in the saline condition, while a high salt level significantly decreased the abundance of nirK and nirS. In addition, the increase of nitrogen concentration attenuated the reduction of nirK, nirS and nosZ gene abundance. Partial least squares regression (PLSR) models demonstrated that salinity, dissolved oxygen (DO) in the overlying water, N concentration, and denitrifying gene abundance were key determinants of the denitrification rate in the saline environment, while pH was an additional determinant in the saline-alkali environment. Taken together, our results suggest that salinity and high pH levels decreased the denitrification rates by significantly inhibiting the abundance of the denitrifying genes nirK, nirS, and nosZ, whereas increasing nitrogen concentration could alleviate this effect. Our study provides helpful information on better understanding of reactive N removal and fertilizer application in the coastal areas.